50 early childhood literacy strategies - Beaty, Janice J. 4 0 16; 5 (Upper Saddle River, New Jersey : Merrill, 2009)
Presents fifty early childhood literacy strategies along with hand-on story activities and drawing and writing exercises.
Includes bibliographical references.
Professional.
Keywords: 2 -- 0; 6; Activity programs. -- Language arts (Early childhood);Early childhood education;Picture books for children.;Language arts.;Early childhood education; 20; 2